The effect of locating and sliding of facet combined with percutaneous endoscopic lumbar discectomy on cell inflammatory indicators and the treatment of disc herniation - Zhang, Qingshan; Du, Peijin; Zhang, Yaning (Cellular and Molecular Biology, 2022)
This study aimed to investigate the effects of IL-8, CRP and TXB2 in the treatment of lumbar disc herniation by combining with percutaneous endoscopic discectomy. For this purpose, 290 patients with disc herniation were selected as the research objects and randomly divided into two groups. The control group was treated with traditional intervertebral fenestration of nucleus pulposus, and the research group was treated with joint process location slip technique combined with percutaneous endoscopic lumbar disc discectomy. The clinical efficacy, functional scores and serological indexes of the two groups were compared, and the prognostic value of IL-8, CRP and TXB2 in the treatment of disc herniation by the combination of the sliding technique of facet location and percutaneous endoscopic discectomy was explored. The results showed that the total effective rate of 95.55% in the study group was higher than 79.31% in the control group, and the difference was significant (P<0.05). The operative time, incision length, length of hospital stay and intraoperative blood loss in the study group were lower than those in the control group (P<0.05). JOA score was higher and ODI score was lower in the two groups after surgery than before surgery, and JOA score in the study group was higher than that in the control group, while the ODI score was lower than that in the control group (P<0.05). Il-8, CRP and MDA in 2 groups increased after the operation, while SOD and TXB2 decreased significantly. Il-8, CRP, TXB2 and SOD in the study group were lower than those in the control group, while MDA was higher than those in the control group (P<0.05). ROC curve indicated that the areas under the curves of IL-8, CRP and TXB2 were 0.725, 0.835 and 0.880, and the areas under the curves, sensitivity and specificity of the combined determination were higher than those of any index (P<0.05). In general, compared with traditional interlaminar fenestration of nucleus pulposus, combined with percutaneous endoscopic lumbar disc discectomy has a significant effect on the treatment of disc herniation, and can reduce the levels of IL-8, CRP and TXB2.